Histórico de Enfermagem: Manejo e Percepções de Enfermeiros no Contexto da Terapia Intensiva Pediátrica - Pinheiro, Jaynara Menezes Sousa (2016)
The Nursing Care Systematization is the methodology used to plan, execute and The Nursing Care Systematization is the methodology used to plan, execute and assess the care, having as essence the care as a working organization tool, the Nursing Process. That is operationalized by a team work, articulated and complementary, enabling the care continuity. The Nursing Process first stage was inserted at the Pediatric Intensive Care Unit of Maranhão Federal University Teaching Hospital in 2013. In the last two years this service has been through a plenty of work staff alterations due to retirement, resignation and new workers hiring. This fact, associated to matters of operation and work process, made us question: what conceptions are revealed by the nurses about the Nursing Process and how they deal with the assistance history operationalization? The research had as objectives: comprehend the nurses’ conceptions about the children care Nursing Process in intensive care; assess the registers and characterize the Nursing History handling in this Intensive Care Unit. It was used the research mixed method combining quantitative and qualitative research with statistical and textual analysis. For data obtainment, it was used the participant observation and primary data collection with the 12 nurses, supported by a questionnaire with open questions analyzed with the Content Analysis methodological support. The research second stage was documental and retrospective using as documental support 72 hospitalized children Nursing Histories in the period between January and August, 2015. For the Nursing History analysis it was used a tool made specifically for this goal, from the items of each Human Basic Need on the same mode they are presented on the Nursing History of the research service context. For the analysis of the Nursing History filling it was used scores which vary from 1 to 189 points. It was classified as Terrible (1 to 66 points); Bad (67 to 100 points); Regular (101 to 145 points); Good or Great (145 or more points). On the qualitative approach two thematic categories were built (Nursing History Valorization and Difficulties on the Nursing History Handling) and seven subcategories (First Contact and Bond Mobilizing Opportunity and Interactive Process; Care Planning and Management Instrument; Individualized and Enlarged Care Strategy; Risks Security and Minimization Resource; Nursing Valorization Instrument; Relative to Working Process; Relative to Nursing History Structure). The qualitative results revealed the nurses assign bureaucratic characteristics to the Nursing History, despite of considering it contributes for the integral care, ample and resolutive on an ambivalent construct between what they think and do as a substantial number of the analyzed items were incomplete or blank. Regarding the Nursing History filling 47,2% were classified as regular, 23,7% bad, 22,2% great and 6,9% terrible. The results characterized the Nursing History handling by nurses of the pediatric intensive care from a subjective and objective perspective of the data analysis revealing it as ambivalent, ambiguous and disqualified in terms of its filling during the nurse care practices.